O papel de atividades lúdicas na produção de textos dissertativos - Silva, Irenilda Francisca de Oliveira e (2006)
Based on an analysis of pupils written production, this work shows that the insertion of play activities in ordinary classroom practices contributes for increasing written language development as well as learning, and to make the teacher/student relationship more pleasant. In this work, the teacher/student relationship carried out through playing activities turns out to be not only a necessary one for a successful educational process, but a stimulus for developing linguistic skills as well. The work shows that pupils attitude with written text changes during the educational process with the development of knowledge and text production, by means of positive responses to playing sessions. The research brings a new form to teaching by calling attention to non-formal aspects and by stimulating the development of critic and analytical sense of higher students with the use of games, playing, music, theater and other activities that enhance the students freedom and expressiveness in the written of texts